The case for health and safety (London, 2010)
"In recent years there has been a growing belief that the workplace is a much safer place than it was, most workers are at little risk, and that as a result much of the regulation that we have is unnecessary. It is this perception that has, in part, led to a growing tendency to dismiss health and safety as being about only factories and mines and which has fed calls for regulations, or enforcement, to be reduced."